Analisis Situasi Masalah Kesehatan Di Kota Depok - Karim, Rohana Rosmiyati Abdul; Djuwita, Ratna; Djadjuli, Hidayat Nur Ghazali (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Indonesia faces a double burden, and the significant increase number of non-communicable diseases also unresolved infectious diseases. Depok City is one of the cities directly adjacent to the capital city of Indonesia. With various health problems occurs, it is necessary to perform a situation analysis to determine the priority health problems in Depok City. This activity uses a descriptive observational design with qualitative and quantitative approaches. The study involves officials at the Depok City Health Office and the Head of the Puskesmas within a total of twenty-eight respondents. Scoring and ranking calculated using the PAHO-adapted Hanlon method with the Basic Priority Rating (BPR) formula. Based on the results of problem identification, ten health problems were obtained: Maternal Mortality Rate, Immunization, Tuberculosis (TBC), Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome, Coronavirus Disease 2019 (Covid-19), Dengue Hemorrhagic Fever, Upper Respiratory Tract Infection, Hypertension, Diabetes Mellitus. and people with severe mental disorders. The results of the assessment of health problems placed Covid-19 (BPR: 58.44), followed by tuberculosis (BPR: 54.34) and Immunization (BPR: 53.66) as the three main priority health problems in Depok City.